1997
DOI: 10.1073/pnas.94.6.2198
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an alternative form of human lactoferrin mRNA that is expressed differentially in normal tissues and tumor-derived cell lines

Abstract: Lactoferrin (LF), traditionally known as an iron-binding protein present in high concentrations in milk and various secretions, has emerged as a multifunctional protein involved in many aspects of the host defense against infection. Recently, LF has been shown to inhibit the growth of solid tumors and reduce experimental metastasis in mice, suggesting that LF also may play a role in the defense against tumorigenesis. Here we provide the sequence of the cDNA and promoter region, the chromosome assignment, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
70
1
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 47 publications
0
70
1
1
Order By: Relevance
“…Discrimination between the 2 isoforms at the mRNA level in the breast cancer cell lines showed that while a decrease in Lf expression was comparable to previously reported studies, ⌬Lf mRNA was not absent from these cells. 9,16,26 -28 In contrast to the data of Siebert and Huang, 9 in which ⌬Lf transcripts were absent after 42 PCR amplification cycles in 10 derived tumor cell lines, we found that ⌬Lf mRNA was in fact present in different breast cancer cell lines after 40 PCR amplification cycles. In fact, in selecting T47D as a representative breast cancer cell line, they unfortunately chose the worst Lf and ⌬Lf messenger-producing cell line according to our results.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Discrimination between the 2 isoforms at the mRNA level in the breast cancer cell lines showed that while a decrease in Lf expression was comparable to previously reported studies, ⌬Lf mRNA was not absent from these cells. 9,16,26 -28 In contrast to the data of Siebert and Huang, 9 in which ⌬Lf transcripts were absent after 42 PCR amplification cycles in 10 derived tumor cell lines, we found that ⌬Lf mRNA was in fact present in different breast cancer cell lines after 40 PCR amplification cycles. In fact, in selecting T47D as a representative breast cancer cell line, they unfortunately chose the worst Lf and ⌬Lf messenger-producing cell line according to our results.…”
Section: Discussioncontrasting
confidence: 56%
“…14 The P2 promoter possesses upstream potential regulatory elements such as XRE, 1/2 HRE, AML-1a and Sp1. 9,10 Recently, it was shown that both promoters contain GGAA motifs for Ets binding and that Ets-1 is a strong regulator of the P2 promoter. 10 Most data in the literature concern the secreted protein Lf, well known as a cationic protein with iron-chelating activity belonging to the transferrin family.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To study the mechanism that regulates LF gene expression in epithelial cells faces a challenge, because the LF gene is permanently silenced in a majority of cancer cells [34][35][36]. Due to the lack of a suitable cell system for mechanistic study, most of the regulatory studies on LF were conducted in animals and in transiently transfected culture cell lines [7,17,37,38].…”
Section: Discussionmentioning
confidence: 99%